Synthesis and Characterization of Biologically Significant Bis-[2-(aryl/furyl)-5-H-4-thiazolidinone]Dapsone Derivatives - Kumar Pataskar, Manish; Rao, J.T. (Asian Journal of Chemistry, 2016)
The heterocyclic compounds containing thiazolidinone moiety have been found to have chemical properties of biological importance; so some new bis[2-(aryl/furyl)-3-H-4-thiazolidinone]dapsone derivatives were prepared. In the synthesis of these compounds dapson was refluxed with different types of aromatic aldehydes to prepare a Schiff base derivative (a). The compound (a) on reaction with thioglycollic acid gives the (bis)-[2-(aryl/furyl)-5-H-4-thiazolidinone]dapsone derivatives (b). The structures of the products were characterized by IR spectral study. All the compounds were evaluated for antifungal and insecticidal activities. Some of the synthesized compounds showed good activity against fungi and insects.